2021
DOI: 10.1038/s41569-021-00598-1
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding avoidance strategies in percutaneous coronary intervention

Abstract: For many years, bleeding has been perceived as an unavoidable consequence of strategies aimed at reducing thrombotic complications in patients undergoing percutaneous coronary intervention (PCI). However, the paradigm has now shifted towards bleeding being recognized as a prognostically unfavourable event to the same extent as having a new or recurrent ischaemic or thrombotic complication. As such, in parallel with progress in device and drug development for PCI, there is clinical interest in developing strate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 158 publications
0
75
0
1
Order By: Relevance
“…20,24 RCTs and meta-analyses have demonstrated that prolonged DAPT after DES implantation increases the risk of bleeding, despite a reduced incidence of ischemic events. 28 These discrepancies may reflect differences in the underlying risks for bleeding, background pharmacotherapy (including selection of P2Y 12 receptor inhibitors), and vascular access site across populations. First, the majority of patients with LMCA disease enrolled in this analysis were at lower risk of bleeding with higher ischemic risk, and the patients who experienced major bleeding or ischemic events during 12 months after an index LMCA PCI were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,24 RCTs and meta-analyses have demonstrated that prolonged DAPT after DES implantation increases the risk of bleeding, despite a reduced incidence of ischemic events. 28 These discrepancies may reflect differences in the underlying risks for bleeding, background pharmacotherapy (including selection of P2Y 12 receptor inhibitors), and vascular access site across populations. First, the majority of patients with LMCA disease enrolled in this analysis were at lower risk of bleeding with higher ischemic risk, and the patients who experienced major bleeding or ischemic events during 12 months after an index LMCA PCI were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Patients at HBR constituted an increasingly prevalent and vulnerable population and posed challenging conundrums in selection of revascularization strategies, as well as antiplatelet treatment and duration for LMCA disease. 29 As bleeding complications after PCI are intrinsically related to the intensity and/or duration of antiplatelet therapy, 28,40 the optimal DAPT duration to HBR patients undergoing LM PCI remains largely unknown. Our results suggested the treatment effects of longer than 12 months of DAPT, consisting of P2Y 12 inhibitor (mainly clopidogrel) and aspirin, on MACCE and clinically relevant bleeding were consistent irrespective of HBR status, reiterating the necessity of clinical and angiographic features contributing to increasing complexity of procedures (ie, LMCA lesion, the extent of coronary artery disease, and complex bifurcation lesion) in guiding clinicians selecting the appropriate DAPT duration following PCI.…”
Section: Circ Cardiovascmentioning
confidence: 99%
“…The cornerstone for risk assessment lies in the assessment of the clinical status, which includes patient history and physical examination, as well as the evaluation of comorbidities and laboratory findings. In patients undergoing PCI, angiographic and procedural features play a key role in determining the risk of ischemic recurrences and should be taken into careful consideration [10]. Accordingly, there is general agreement that the optimal strategy for balancing the risk of ischemia and bleeding after PCI lies in an integrated assessment of three key factors: bleeding risk, ischemic risk and responsiveness to an antiplatelet agent (Figure 2) [10].…”
Section: Balancing the Risk Of Ischemia And Bleeding After Pcimentioning
confidence: 99%
“…In patients undergoing PCI, angiographic and procedural features play a key role in determining the risk of ischemic recurrences and should be taken into careful consideration [10]. Accordingly, there is general agreement that the optimal strategy for balancing the risk of ischemia and bleeding after PCI lies in an integrated assessment of three key factors: bleeding risk, ischemic risk and responsiveness to an antiplatelet agent (Figure 2) [10]. In this respect, risk algorithms and scores are crucial for weighing the value of individual clinical, laboratory and procedural features.…”
Section: Balancing the Risk Of Ischemia And Bleeding After Pcimentioning
confidence: 99%
See 1 more Smart Citation